Digital Applications and The Use of Information Technology in Increasing the Attractiveness of Foreign Tourist Visits - Dessy Hariyanti, Ni Kadek; Noviani, Lona; Khairani, Elisa; Latief, Yanuar; Mustafa, Fahrina (International Journal of Engineering, Science and Information Technology, 2024)
This study aims to analyze the role of the adoption of technology and digital devices in facilitating business processes in the tourism industry in terms of delivering interactive information to tourists, especially foreign tourists. This study uses a qualitative method. Data collection methods used in the study are literature reviews, field surveys, and observations. The results of the study show that many foreign tourists are active and regular in using information and communication technology with laptops, smartphones, and the Internet. The results of the study also concluded that applications such as digital maps are the most popular devices for planning travel. Although the demand for digital solutions is very high, there is a gap between the technology preferences of foreign tourists and the ability of industry players to adopt technology, the majority of tourism industry players still rely on conventional methods. Foreign tourists who are currently dominated by the digital generation show a fast understanding and adaptation of technology, this should be responded to quickly by tourism business actors in Indonesia in developing digital devices. The tourism sector needs to improve technology integration to improve the efficiency and relevance of information services. To meet the needs of foreign tourists and technology-savvy tourists, it is important to develop technological devices that can be used to provide information and are easily accessible